HUBUNGAN PENGETAHUAN ORANG TUA TENTANG DEMAM THYPOID DENGAN KEBIASAAN JAJAN PADA SISWA SDN 3 CANDISARI GROBOGAN PURWODADI - Diyono -; Ariawan Tri Susanto; Gidheon Edhi Mukti (Sekolah Tinggi Ilmu Kesehatan Panti Kosala, 2015)
AbstractIntroduction: Thypoid Fever is gastrointestinal infection caused by salmonella thyposa that influx into the intestine. The incidence of the disease the higher,including the students of SDN Candisari 3. Thypoid Fever can be prevented by reducing snack food habits that are less clean. Knowledge of parents about Thypoid Fever have an important role in reducing snack habits in children.Purpose of the study: (1) determine the level of knowledge of parental descriptions of disease typhoid fever (2) find a deskription snack habits in primary school students (3) determine the relationship of the level of parental knowledge about the disease typhoid fever with habit of eating snacks in elementary school students Candisari 3 Grobogan Purwodadi.Design: Type of research a descriptive analytic study with correlation designSubjects: The study population is students and parents of students of SDN School 3 Candisari. The sample size of 60 students and parents by using quota sampling.Results: (1) The level of parental knowledge about the disease typhoid fever were high for the value - average 23.02. The percentage level of knowledge of parents with a high category is 85%, the medium category being 15%, and low categories of 0%. (2) The habit of eating snacks to students including lowcategory (5.18) where the percentage of moderate category 13.33%, 18.33% and the most category is severe of 68.33%. (3) There is no significant relationship between the level of parental knowledge about the disease typhoid fever with snack habits in students, where the results of chi square test p =0.258.Conclusion: The level of parental knowledge about diseases of the Thypoid Fever not have a relationship with the habit of eating snacks in elementary school.Keywords: Thypoid Fever, Level of Knowledge, Snack Habits